ASPECTS OF RELIGIOUS AND AXIOLOGICAL INFLUENCE OF THE ISLAMIC INTERNET COMMUNICATIONS - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with aspects of religious and axiological influence of the Internet communication. Its impact on society has been revealed.